2022
DOI: 10.1186/s12938-022-01005-7
|View full text |Cite
|
Sign up to set email alerts
|

Detecting bone lesions in the emergency room with medical infrared thermography

Abstract: Introduction Low- to high-energy impact trauma may cause from small fissures up to extended bone losses, which can be classified as closed or opened injuries (when they are visible at a naked eye). Objective The aim of this study was to investigate the feasibility of clinical diagnosis of bone trauma through medical infrared thermography, in a hospital emergency room. Methods Forty-five patients with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The majority of authors identified their studies as exploratory or assessing feasibility ( n = 16) ( 11 , 12 , 14–16 , 19 , 21 , 22 , 26 , 27 , 31 , 32 , 34 , 35 , 37 , 39 ). Few were described as validation or diagnostic accuracy studies ( n = 8) ( 13 , 17 , 18 , 20 , 24 , 33 , 36 , 38 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of authors identified their studies as exploratory or assessing feasibility ( n = 16) ( 11 , 12 , 14–16 , 19 , 21 , 22 , 26 , 27 , 31 , 32 , 34 , 35 , 37 , 39 ). Few were described as validation or diagnostic accuracy studies ( n = 8) ( 13 , 17 , 18 , 20 , 24 , 33 , 36 , 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two described the requirement of a standardised environment as potentially limiting the applicability of IRT to clinical practise ( 14 , 18 ). The need to remove skin coverings to enable the device to be used was frequently mentioned ( 11 , 19 , 20 , 31–33 , 35 , 38 ). Anti-inflammatory use, peripheral vascular disease and ice pack application were identified as potential confounders that excluded some recruits from study participation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A related study compared the temperature difference between forearm fractures and the contralateral uninjured side in 19 children aged 4-14 years and found an increase in the temperature of the injured area followed by a reduction in the following weeks [15]. Infrared thermal imaging has been applied to detect fractures associated with leg, hand, forearm, clavicle, foot, and ankle in a study involving 45 patients [16]. The study concluded that infrared thermal imaging could be a valuable complementary diagnostic modality to the X-ray radiograph.…”
Section: Infrared Imaging and Its Application In Bone Fracture Detectionmentioning
confidence: 99%
“…Moreover, an alcohol sensor can measure the alcohol level of the rider and lock the ignition system if the level is above a certain threshold [ 22 ]. For first responders, a smart helmet can provide a thermal scan of an individual to check for COVID-19 symptoms [ 23 ] or injuries such as broken bones [ 24 ] or bleeding [ 25 ]. An IoT smart helmet can also track the status of the response crew in real time and report back to a central control center [ 23 ].…”
Section: Introductionmentioning
confidence: 99%